Mobility particle size spectrometers: Calibration procedures and measurement uncertainties. Issue 2 (1st February 2018) - Wiedensohler, A.; Wiesner, A.; Weinhold, K.; Birmili, W.; Hermann, M.; Merkel, M.; Müller, T.; Pfeifer, S.; Schmidt, A.; Tuch, T.; Velarde, F.; Quincey, P.; et al.
ABSTRACT: Mobility particle size spectrometers (MPSS) belong to the essential instruments in aerosol science that determine the particle number size distribution (PNSD) in the submicrometer size range. Following calibration procedures and target uncertainties against standards and reference instruments are suggested for a complete MPSS quality assurance program: (a) calibration of the CPC counting efficiency curve (within 5% for the plateau counting efficiency; within 1 nm for the 50% detection efficiency diameter), (b) sizing calibration of the MPSS, using a certified polystyrene latex (PSL) particle size standard at 203 nm (within 3%), (c) intercomparison of the PNSD of the MPSS (within 10% and 20% of the dN/dlogDP concentration for the particle size range 20–200 and 200–800 nm, respectively), and (d) intercomparison of the integral PNC of the MPSS (within 10%). Furthermore, following measurement uncertainties have been investigated: (a) PSL particle size standards in the range from 100 to 500 nm match within 1% after sizing calibration at 203 nm. (b) Bipolar diffusion chargers based on the radioactive nuclides Kr 85, Am 241, and Ni 63 and a new ionizer based on corona discharge follow the recommended bipolar charge distribution, while soft X-ray-based charges may alter faster than expected. (c) The use of a positive high voltage supply show a 10% better performance than a negative one. (d) The intercomparison of the integral PNC of an MPSS against the total number concentration is still within the target uncertainty at an ambient pressure of approximately 500 hPa. Copyright © 2018 Published with license by American Association for Aerosol Research